2016
DOI: 10.1148/rg.2016150084
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced Reformatted MR Images for Preoperative Assessment of the Bridging Veins of the Skull Base

Abstract: Magnetic resonance (MR) venography and computed tomographic (CT) venography are suited for displaying the convexity veins that drain the medial and lateral surfaces of the brain hemispheres. However, such is not the case for the bridging veins of the skull base. Technical factors prevent contrast material-enhanced MR or CT images obtained in standard axial, coronal, and sagittal planes from fully displaying the curved pathways of these clinically important venous structures. This limitation can be overcome by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…The occurrence of the SSV in the present study is lower than that reported by Kawamata et al who reported a 99.2% presence in the left hemisphere and 95.1% in the right cerebral hemisphere 20 . Wangaryattawanich et al stated that the SSV may be absent in 9.0-10.0% of individuals; this statement is corroborated by the study conducted by Kazumata et al, who reported an absent or hypoplastic SSV in 10.0% of the sample 12,21 . In the absence of the SSV, the territory is drained by the deep system of cortical veins, or the adjacent AV 12,22 .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The occurrence of the SSV in the present study is lower than that reported by Kawamata et al who reported a 99.2% presence in the left hemisphere and 95.1% in the right cerebral hemisphere 20 . Wangaryattawanich et al stated that the SSV may be absent in 9.0-10.0% of individuals; this statement is corroborated by the study conducted by Kazumata et al, who reported an absent or hypoplastic SSV in 10.0% of the sample 12,21 . In the absence of the SSV, the territory is drained by the deep system of cortical veins, or the adjacent AV 12,22 .…”
Section: Discussionmentioning
confidence: 73%
“…The largest anastomotic channel connecting the SSV and transverse sinus is the VL 11,12 . The VL originates in the posterior aspect of the lateral ssure and courses obliquely over the occipitotemporal sulcus, as well as the inferolateral aspect of the temporal lobe, to project posteroinferiorly into the transverse sinus 9,12 . The VT is the largest vein that crosses the lateral surface of the frontal or parietal lobes between the SSV and superior sagittal sinus 5,8 .…”
Section: Introductionmentioning
confidence: 99%
“…The superior cerebral veins (SCVs, TA code A12.3.06.003) are superficial veins lying on the surface of the cerebral cortex, draining mainly into several groups of cortical bridging veins (Kiliç & Akakin, 2008). The superior sagittal sinus (SSS) receives many such veins mainly from the superior part of the medial and lateral surfaces of the frontal, parietal, and occipital lobes (Mortazavi et al, 2013; O'Connell, 1934; Wangaryattawanich et al, 2016). The SCVs are key vascular tributaries within the intracranial venous system because they drain blood into the dural sinuses and, subsequently, into the internal jugular veins for return to the central circulation (Mortazavi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The superior cerebral veins (SCVs, TA code A12.3.06.003) are superficial veins lying on the surface of the cerebral cortex, draining mainly into several groups of cortical bridging veins (Kiliç & Akakin, 2008). The superior sagittal sinus (SSS) receives many such veins mainly from the superior part of the medial and lateral surfaces of the frontal, parietal, and occipital lobes (Mortazavi et al, 2013;O'Connell, 1934;Wangaryattawanich et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Superficial veins lie on the surface of the cerebral cortex and drain mainly into several groups of cortical bridging veins (CBVs). The superior sagittal sinus (SSS) receives many such CBVs mainly from the superior part of the medial and lateral surfaces of the frontal, parietal, and occipital lobes (O'Connell, ; Mortazavi et al, ; Wangaryattawanich et al, ).…”
Section: Introductionmentioning
confidence: 99%